أثر الابتكار التسويقي علي رضا العملاء في المصارف: دراسة تطبيقية على مصرف الجمهورية فرع عين زارة وفرع برج طرابلس - الطيب جمعة محمد ابوليفة (Surman Journal of Science and Technology, 2025)
The study aimed to identify the level of marketing innovation in the bank under study, measure the level of customer satisfaction, and analyze the effect of the dimensions of marketing innovation on customer satisfaction. It also sought to determine the extent to which marketing innovation can be applied in commercial banks, The study adopted the descriptive analytical approach and used the questionnaire as the main tool for data collection. The questionnaire included sections related to demographic data, the dimensions of marketing innovation, and customer satisfaction. A number of questionnaires were distributed, and after excluding the invalid ones, the number of questionnaires suitable for analysis reached 70. The data were analyzed using the Statistical Package for the Social Sciences (SPSS). The reliability results showed that the overall Cronbach’s Alpha coefficient for the questionnaire was 88.2%, indicating that the study instrument had an excellent level of reliability, The descriptive results revealed that the level of marketing innovation in the bank was low across most dimensions. The mean score for innovation in services was 2.44, for pricing innovation 2.13, for promotional innovation 2.17, and for distribution innovation 2.53. These indicators suggest that the bank still needs to strengthen marketing innovation practices in its banking services. The results also showed that the overall mean score for customer satisfaction was 2.05, which represents a low level, indicating weak customer satisfaction with the services provided, as for the hypothesis testing results, they revealed a statistically significant positive relationship between marketing innovation and customer satisfaction. The correlation coefficient reached 0.448, while the coefficient of determination was R² = 0.201. This means that marketing innovation explains 20.1% of the variation in customer satisfaction. Accordingly, improving marketing innovation practices within the bank can contribute to increasing the level of customer satisfaction, although other factors may also influence customer satisfaction, The study recommends that the management of Jumhouria Bank should pay greater attention to strengthening marketing innovation practices in their various dimensions, particularly innovation in services, pricing, promotion, and distribution, due to their positive impact on improving customer satisfaction. The study also recommends developing electronic banking services, updating automated teller machines (ATMs), adopting modern digital promotional methods, and measuring customer satisfaction periodically.